2008
DOI: 10.1118/1.2940604
|View full text |Cite
|
Sign up to set email alerts
|

COMS eye plaque brachytherapy dosimetry simulations for P103d, I125, and C131s

Abstract: Monte Carlo (MC) simulations were performed to estimate brachytherapy dose distributions for Collaborative Ocular Melanoma Study (COMS) eye plaques. Brachytherapy seed models 200, 6711, and CS-1 Rev2 carrying 103Pd, 125I, and 131Cs radionuclides, respectively, were modeled and benchmarked against previously published values. Calculated dose rate constants MClambda were 0.684, 0.924, and 1.052 cGy h(-1) U(-1) (+/- 2.6%, k = 1 uncertainty) for models 200, 6711, and CS-1 Rev2, respectively. The seeds were distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(120 citation statements)
references
References 16 publications
3
112
0
2
Order By: Relevance
“…This is in contrast to the dose modifying effects of the more commonly used COMS plaque, for which studies have shown a hetero/homo-ratio consistently below 1.00, mainly due to attenuation in the silastic seed carrier (11,14,23 mm, i.e. with the apex located at least 7 mm from the plaque surface.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…This is in contrast to the dose modifying effects of the more commonly used COMS plaque, for which studies have shown a hetero/homo-ratio consistently below 1.00, mainly due to attenuation in the silastic seed carrier (11,14,23 mm, i.e. with the apex located at least 7 mm from the plaque surface.…”
Section: Discussionmentioning
confidence: 50%
“…While the COMS system uses silastic seed carriers that establish fixed seed positions and a distinct distance to the sclera, seeds are attached manually to the St. Erik plaque using a thin layer of silicone rubber glue. 125 I seeds, the dose reduction is on the order of 13-14% at 10 mm depth from inner sclera, compared to TG-43 conditions (11,14). Another plaque design, the OSU-NAG plaque, has similarities with the St. Erik plaque in that the seeds are manually glued instead of being positioned in a seed carrier (as for COMS plaques) (15,16).…”
Section: The Collaborative Ocular Melanoma Study (Coms) Was Initiatedmentioning
confidence: 99%
“…56 In water and vacuum, 10 11 and 10 10 photon histories were simulated to achieve negligible statistical uncertainties. Air kerma was scored using a 5 keV energy cutoff in vacuum 30 cm from the source in a voxel covering 90.0°AE 7.5°whose center was positioned on the source transverse plane to approximate 112 reported MC results in water from 0.1 cm to 7 cm, and Zhang et al 115 reported MC results in water from 0.05 cm to 10 cm. Comparing these data to those from Rivard at common distances, agreement of results from Wang and Zhang with Rivard was within 0.3% on average with a maximum discrepancy of 1.6%.…”
Section: A103 Model Iapd-103a Anisotropy Functionsmentioning
confidence: 99%
“…Melhus and Rivard 112 reported results of MC calculations on the dosimetry parameters for the model CS-1 Rev2 131 Cs source using the MCNP5 (version 1.40) photon transport simulation code, principally for evaluating eye plaque dose distributions and benchmarking a 3-radionuclide dosimetry comparison. The default photoatomic cross-section libraries based on ENDF/B-VI 72 were used, along with the 131 Cs photon spectrum taken from the NNDC and mass-energy absorption coefficients from the NIST XCOM database to convert *F4 photon energy fluence to absorbed dose.…”
Section: A103 Model Iapd-103a Anisotropy Functionsmentioning
confidence: 99%
“…For example Granero et al, 2004 calculated the dose rate around the eye plaque loaded with 125 I sources in Acrylic insert and they found Acrylic insert has no attenuation effect on dose rate and the presence of acrylic insert can be negligible in the calculations. In other Mont Carlo simulations Chiu-Tsao et al, 1993, obtained 10% dose reduction at 1cm for Silastic insert; Thomson et al, 2008 reported 17% dose reduction for 103 Pd seed at distance of 1 cm in eye plaque due to presence of Silastic insert; and also calculated results by (Melhus & Rivard, 2008) demonstrated approximately 22.6%±0.5%, 13.0%±0.3%, and 10.8%±0.3% more in each 103 Pd, 125 I, and 131 Cs seed contained in a eye plaque, respectively was required to deliver the same dose to the apex of tumor. According to the Monte Carlo calculated data, size, shape and location of the eye tumor, standard eye plaque should design.…”
Section: Other Application Of Monte Carlomentioning
confidence: 99%